An outbreak of multiple genotypes of Listeria monocytogenes in New Zealand linked to contaminated ready‐to‐eat meats—a retrospective analysis using whole‐genome sequencing. (1st December 2019) - Rivas, L.; Dupont, P.‐Y.; Wilson, M.; Rohleder, M.; Gilpin, B.
Abstract: Four cases of listeriosis in a hospital (A) in New Zealand were identified in 2012. Pulsed‐field gel electrophoresis (PFGE) used at the time identified four pulsotypes amongst the clinical isolates. Two of the pulsotypes matched to Listeria monocytogenes isolates obtained from ready‐to‐eat (RTE) meat samples from a RTE producer tested during a nationwide microbiological survey the month prior. The outbreak investigation confirmed that the RTE producer had supplied product to the hospital and additional testing confirmed the presence of L. monocytogenes in RTE meats from the hospital kitchen. Two further listeriosis cases presented in another hospital (B) with one clinical isolate identified as the same pulsotype as identified for one case in hospital A, but the epidemiology information concluded that the clinical cases from hospital B were not linked to the outbreak. Retrospective whole‐genome sequencing confirmed that epidemiologically linked isolates belonging to three different genotypes for clinical cases from hospital A and RTE meats samples from the hospital kitchen differed by 0‐1 core‐genome locus or single nucleotide polymorphisms (SNP). The use of core‐genome multilocus sequence typing and SNP analysis provided a greater degree of discrimination between isolates compared to PFGE. Significance and Impact of the Study: This study describes a listeriosis outbreak associated with a hospital in New Zealand and attributed to contaminated ready‐to‐eat (RTE) meat supplied to the hospital by a single producer. Retrospective whole‐genome sequence analysis of outbreak isolates was found to provide a greater degree of discrimination between isolates compared to pulsed‐field gel electrophoresis and supported the conclusions made at the time of the outbreak. The multiple genotypes identified from clinical cases and the RTE meats obtained during the outbreak highlight the importance of epidemiological concordance alongside genotyping.